Cardioprotective Effects of QiShenYiQi Dripping Pills on Transverse Aortic Constriction-Induced Heart Failure in Mice - Ruan, Guoran; Ren, Haojin; Zhang, Chi; Zhu, Xiaogang; Xu, Chao; Wang, Liyue (Frontiers in Physiology, 2018)
QiShenYiQi dripping pills (QSYQ), a traditional Chinese medicine, are commonly used to treat coronary heart disease, and QSYQ was recently approved as a complementary treatment for ischemic heart failure in China. However, only few studies reported on whether QSYQ exerts a protective effect on heart failure induced by pressure overload. In this study, we explored the role of QSYQ in a mouse model of heart failure induced by transverse aortic constriction (TAC). 28 C57BL/6J mice were divided into four groups: Sham + NS group, Sham + QSYQ group, TAC + NS group, and TAC + QSYQ group. QSYQ dissolved in normal saline (NS) was administered intragastrically (3.5 mg/100 g/day) in the Sham + QSYQ and TAC + QSYQ groups. In the Sham + NS and TAC + NS groups, NS was provided every day intragastrically. Eight weeks after TAC, echocardiography and cardiac catheterization were performed to evaluate the cardiac function, and immunofluorescent staining with anti-actinin2 antibody was performed to determine the structure of the myocardial fibers. Moreover, TUNEL staining and Masson trichrome staining were employed to assess the effects of QSYQ on cardiac apoptosis and cardiac fibrosis. Western blots and real-time polymerase chain reaction (PCR) were used to measure the expression levels of vascular endothelial growth factor (VEGF) in the heart, and immunohistochemical staining with anti-CD31 antibody was performed to explore the role of QSYQ in cardiac angiogenesis. Results showed that TAC-induced cardiac dysfunction and disrupted structure of myocardial fibers significantly improved after QSYQ treatment. Moreover, QSYQ treatment also significantly improved cardiac apoptosis and cardiac fibrosis in TAC-induced heart failure, which was accompanied by an increase in VEGF expression levels and maintenance of microvessel density in the heart. In conclusion, QSYQ exerts a protective effect on TAC-induced heart failure, which could be attributed to enhanced cardiac angiogenesis, which is closely related to QSYQ. Thus, QSYQ may be a promising traditional Chinese medicine for the treatment of heart failure induced by pressure overload such as hypertension.